Angle-resolved photoemission studies of adsorbed hydrocarbons - Steinrück, Hans-Peter (Journal of Physics: Condensed Matter, 1996)
Angle-resolved UV photoelectron spectroscopy is used to investigate the electronic structure and bonding of adsorbed hydrocarbons, the orientation and symmetry of the adsorbate on the surface, the influence of lateral interactions, and the formation of two-dimensional adsorbate band structures. Several examples of simple hydrocarbon molecules such as benzene, ethylene and acetylene adsorbed on Ni(110), Ni(111), Ru(001) and the reconstructed Pt(110)1x2 surface are presented. The experimental studies are accompanied by theoretical calculation. In addition some special aspects of the photoemission process, namely the photoionization cross section and vibronic coupling, are discussed.